Operacional ou estratégica?: um estudo de caso sobre a Comunicação com empregados nas indústrias criativas do Recife. - Queiroz, Sabrina Medeiros Wanderley de (2020)
This research aims to identify how the relationship between management and employees within the Creative Industries is established through organizational communication. In this context, it is sought to identify the channels adopted by these organizations to share institutional information with the internal public. For that, a documentary analysis was conducted in industries in the areas of games, audiovisual and music, with headquarters in Recife, representing the sectors that most bill in the segment of the creative economy of the State, according to data from the Digital Port. In order to interpret if the results obtained present cultural traits that characterize this type of industry, we sought to build on a theoretical-conceptual review in the field of organizations, organizational communication and creative industries, in order to contextualize the main changes that have impacted the relationship between employees in the XX and XXI centuries, and the relation of this industrial development to the advance and importance of internal communication in companies.